Analysis of Mental Workload on Counter Sales Using NASA-TLX Method - Safitri Ramadhani, Dinda; Soraya Putri, Arinda; Ambarwati, Niken Fauziah (Metris: Jurnal Sains dan Teknologi, 2023)
PT. XYZ is a service-oriented branch company that provides consumers with a wide range of products. Services provided by this company is divided into three main sections, namely sales, service, and spare part. One of the main parts is sales, which is selling units of cars carried out by counter sales to meet targets. The demand for achieving targets provides a psychological workload for counter sales. Therefore, it is necessary to measure the mental workload in this area. The work measurement method used in this research is NASA-TLX. This method was developed based on the emergence of subjective measurement needs in measuring workload using six indicators, namely mental demand, physical demand, temporal demand, own performance, effort, and level of frustration. The results showed that WWL values ​​were in the range of 88.33-91.67 and had a very high category. Several recommendations for improvement that need to be implemented include evaluating picket scheduling by considering predictions of increased customer visits, conducting routine training and providing motivation, and providing rewards as a form of appreciation for workers according to their achievements.